Promosi Perpustakaan Melalui Media Sosial Di Perpustakaan IAIN Salatiga - Ifonilla Yenianti (Pustabiblia: Journal of Library and Information Science, 2019)
One of the five laws of the library is that a library is a growing organism.  Library is not an institution in the "static" or "silent" condition, but the library will be follow and adjust the development of the times  dynamically. The development of the library that is currently in the 21st century is definitely different from the development of the library in the 19th century, not only in terms of the development of this writing takes the theme of library promotion by looking directly at the role of the Salatiga IAIN library in carrying out various promotional activities. This writing of this article using the ethnographic approach in order to describe the culture of the library in terms of promotion. The conclusion of this article is promotion as one of the activities of library marketing (library marketing) and be come the key of the continued use of the library by its users. Likewise the existence of social media is not a competitor but rather a means for promotion that makes it easy for librarians to communicate with users. The Salatiga IAIN Library uses social media in the form of websites and youtube accounts as promotional media to communicate its services, activities and wealth of reference resources to users.